Sarcoidosis Confined to the Airway Masquerading as Asthma - George Mixides; Elizabeth Guy (Canadian Respiratory Journal)
A rare case of sarcoidosis is presented. A 32-year-old white woman initially diagnosed with asthma was to undergo thyroidectomy to eliminate what was thought to be the real source of her symptoms. Instead, the cause was found to be sarcoidosis involving only the major airways, without intrathoracic adenopathy, atelectasis, pulmonary parenchymal infiltrates or evidence of extra pulmonary disease. She rapidly responded to systemic glucocorticoids, which later was supplemented successfully by inhaled glucocorticoids for persistent cough.